METAFORA AS AN OBJECT OF SCIENTIFIC RESEARCH OF COGNITIVE LINGUISTICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article reveals the stylistic specificity of the poet through the study of metaphors in the poetry of Shavkat Rahmon from a cognitive point of view.